Addressing Accountability and Fair Practices in Labor Contracting for Sustainable Harvesting in the Sugar Industry - Bhujbal Shravan Vijaykmar; Renuka Kale; Bhushan M. Borhade; Sanjay Patil; Amey C. Deshpande; Devyani V. Jarad (International Journal of Solid State Innovations & Research, 2024)
This study promotes the use of blockchain technology to solve issues with labor data management in the sugar business. Through decentralized blockchain storage, the proposed solution protects the security and openness of labor data, with an emphasis on preventing unethical activity by contractors holding numerous simultaneous contracts. Smart contracts make it easier for contractors to register and keep track of engagements, which helps the sugar industry enforce contractual compliance and confirm authenticity. In addition to reducing the possibility of abuse and false information, this blockchain-based approach lays the groundwork for a more responsible and effective labor management system, which will promote integrity and confidence in the sugar sector.
Keywords: Blockchain technology; Contractors; Transparency; decentralized storage; efficient labor management; security; smart contracts